Tuberculose na população indígena e não indígena da Terra Indígena de Parabubure MT nos anos de 2009 a 2017 - Ocampos, Lauren Cristiane Leite (2018)
Tuberculosis deserves special care from health professionals and the population due to the impact on morbidity and mortality that end up influencing the quality of life. The objective of the study was to analyze the incidence and factors associated with ILTB cases and active tuberculosis cases in the indigenous population and non-indigenous population of TI in Parabubure, MT, from 2009 to 2017. Methodology: This is a quantitative study of mixed approach, the first epidemiological, descriptive and retrospective study of cases of latent infection and active cases of tuberculosis registered in Parabubure IT in the years 2009 to 2017; and the second ecological study of the temporal type, incidence rates of active tuberculosis and ILTB cases in the general population and in the indigenous and nonindigenous race / color group from 2009 to 2017, both studies being based on secondary data from demographic censuses of 2000 and 2010, the SINAN and ILTB information system of COVEP of SES / MT. Outcome: In the period from 2009 to 2017, 194 ILTB cases were reported in Parabubure IT. The annual distribution of ILTB notifications revealed that there was an increase in the year 2015 that were 72 cases, and in the year 2016 that were 75 cases, all cases being registered in indigenous. The age groups 5 to 9 years and 20 to 34 years present the highest percentage of cases of ILTB (22.30% and 20.31%), respectively. The clinical-epidemiological profiles of the ILTB cases reported showed that 42.92% were natives who had contact with bacilliferous, in relation to race / color, we observed that this item is not included in the ILTB notification and investigation form. Identification of the patient and the area of residence in each municipality, where it was verified that 452 (99.78%) were indigenous. When comparing the active cases of tuberculosis between indigenous and nonindigenous SINAN regarding the gender variable, it is observed that a greater percentage occurred in indigenous females (51.62%); the most affected age group were young adults; chest radiography in which (95.43%) of the natives and (87.50%) of the nonindigenous showed results suggestive of tuberculosis; the gross incidence rate of active tuberculosis cases registered in Parabubure IT in 2014 had a large increase reaching 101.20 / 100,000 inhabitants, when we analyzed separately the incidence between indigenous and nonindigenous people we noticed the higher incidence among indigenous people, also showing an increase Conclusions: The research findings show the social inequalities in the occurrence of tuberculosis and reinforce the need for effective public policies in confronting ILTB and active tuberculosis cases, especially in part of Parabubure IT.